On estimates for the parameters of a Gaussian stationary process with the spectral density [P(iλ)]^-2 - Pisarenko, V. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Ф. Писаренко. Об оценках параметров гауссовского стационарного процесса со спектральной плотностью [P(iλ)]^-2 V. Pisarenko. Apie stacionaraus Gauso proceso su spektriniu tankiu [P(iλ)]^-2 parametrų įvertinimus